SEXUAL OFFENCES IN POLAND IN A STATISTICAL PERSPECTIVE – SELECTED ISSUES - Poniatowski, Piotr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to analyse selected statistical data on final convictions for sexual offences in Poland. Methods: a statistical method was used to analyse data on the number of final convictions and the types of penalties imposed. Results: convictions for sexual offences in Poland represent a small proportion of convictions for all offences in recent years. In 2018, the highest number of convictions among sexual offences concerned the offence of rape (Article 197 of the Polish Penal Code) and sexual acts with a minor under the age of 15 (Article 200 § 1 of the Polish Penal Code – the so-called offence of paedophilia). The indicated sexual offences are in most cases punished with imprisonment, while in 2018 these were mainly imprisonment penalties without conditional suspension of their execution (absolute imprisonment). These penalties in 2018 in most cases did not exceed half of the upper level of the statutory limits of the penalty, and were often adjudicated at the minimum level. Discussion: taking into account statistics on convictions for sexual offences, one may come to the conclusion that the threat of such acts is quite low in Poland. However, it should be remembered that sexual crime is stigmatized by a very large so-called ‘dark number’ (comitted crimes that are not covered by crime statistics because they are not been disclosed by law enforcement authorities). The majority of convictions concern the most reprehensible sexual offences (rape, paedophilia). It is worth noting that Polish courts are quite lenient towards perpetrators of the indicated crimes.